PEMBAHARUAN ANALISIS JABATAN DAN ANALISIS BEBAN KERJA DI LINGKUP DINAS PETERNAKAN DAN KESEHATAN HEWAN KABUPATEN TAKALAR - Adrianti; Rasdiyanti, Andi (Politeknik STIA LAN Makassar, 2025)
The restructuring of job nomenclature for operational positions within government bureaucracy institutions requires each agency to revised their job analysis and workload documents accordingly. Previously, operational job guidelines were based on the Regulation of the Minister of Administrative and Bureaucratic Reform Number 41 of 2018. However, this has now been replaced by Ministerial Decree Number 11 of 2024. Despite this change, the Department of Livestock and Animal Health of Takalar Regency continues to utilize job and workload analysis documents that refer to the outdated nomenclature. This study aims to update these document in alignment with the most recent regulatory standards for operational job titles. The revision particularly focuses on positions under the Division of Animal Health and Veterinary Public Health, as well as the Division of Extension and Business Development. A qualitative descriptive method was employed, incorporating techniques such as data collection, data reduction, data presentation, and verification. The outcomes of this research include updated job and workload analysis documents containing 17 key job information components, in accordance with the Ministerial Regulation Number 1 of 2020 concerning Guidelines for Job Analysis and Workload Analysis.